Stand age drives rhizosphere soil inorganic nitrogen availability under nitrogen deposition in subtropical Machilus pauhoi plantations - Binfeng Yang; Yao Liu; Dongliang Cheng; Chaobin Xu; Fengna Liang; Quanlin Zhong (Forest Ecology and Management, 2026)

Dynamic performance of one-part ultra-high-performance geopolymer concrete composite slabs subjected to long-duration blast loading - Yuanzheng Lin; Yuanfeng Zhen; Yufei Yan; Zhouhong Zong; Minghong Li; Chaobin Yang; Hanyuan Shi; Jingming Cai (Engineering Structures, 2026)

Can saturated fatty acids spare essential fatty acids in freshwater fish? Evidence from growth, metabolism and gut microbiota in common carp (Cyprinus carpio) - Yang Long; Zhiyi Cheng; Rui Li; Zeliang Su; Chaobin Qin; Guoxing Nie; Yuanyou Li; Dizhi Xie (Animal Feed Science and Technology, 2026)

Lactiplantibacillus plantarum Ameliorated Growth Performance and Intestinal Inflammation by Modulating Gut Microbial Structure and Function of Yellow River Carp (Cyprinus carpio) - Lijiao Cheng; Junxiang Ding; Wenli Liu; Yijie Li; Chaobin Qin; Liping Yang; Xiao Yan; Guoxing Nie (Probiotics and Antimicrobial Proteins, 2026)

Assessing heat-related health risk based on the hazard–exposure–vulnerability framework in Shenzhen, China: A block-level local climate zone perspective - Lilong Yang; Chaobin Yang; Weiqi Zhou; Lifeng Liu; Chao Wang (Journal of Cleaner Production, 2025)

The adaptation of Machilus pauhoi cuttings to nitrogen deposition and seasonal drought stress is superior to seedlings - Binfeng Yang; Fengna Liang; Tingting Kang; Yonghong Wu; Chaobin Xu; Dongliang Cheng; Quanlin Zhong (Forest Ecology and Management, 2025)

Experimental and numerical study of one-part ultra-high performance geopolymer concrete slabs subjected to blast loading - Yuanzheng Lin; Yufei Yan; Yuanfeng Zhen; Zhouhong Zong; Minghong Li; Hanyuan Shi; Chaobin Yang; Haimin Qian; Jingming Cai (Engineering Structures, 2025)

Effects of maternal PM2.5 exposure during pregnancy on cardiovascular maldevelopment in rat offspring - Shengying Yang; Guiming Zhang; Xinru Hong; Tao Li; Yang Liu; Huangfeng Hong; Lina Liu; Hailong Wang; Shuiping Wu; Yulan Wang; Ping Wang; Qinghua Sun; et al. (Reproductive Toxicology, 2025)

In vivo imaging to trace the dissemination of Aeromonas hydrophila in common carp (Cyprinus carpio) after intestinal infection - Yiran Wang; Yijie Li; Piao Wang; Chunchun Yang; Shaoyang Zhi; Chaobin Qi; Guoxing Nie; Junli Wang (Fish & Shellfish Immunology, 2025)

Multi-Temporal Energy Management Strategy for Fuel Cell Ships Considering Power Source Lifespan Decay Synergy - Xingwei Zhou; Xiangguo Yang; Mengni Zhou; Lin Liu; Song Niu; Chaobin Zhou; Yufan Wang (Journal of Marine Science and Engineering, 2024)
With increasingly stringent maritime environmental regulations, hybrid fuel cell ships have garnered significant attention due to their advantages in low emissions and high efficiency. However, challenges related to the coordinated control of multi-energy systems and fuel cell degradation remain significant barriers to their practical implementation. This paper proposes an innovative multi-timescale energy management strategy that focuses on optimizing the lifespan decay synergy of fuel cells and lithium batteries. The study designs an attention-based CNN-LSTM hybrid model for power prediction and constructs a two-stage optimization framework: The first stage employs Model Predictive Control (MPC) for long-term power planning to optimize equivalent hydrogen consumption, while the second stage focuses on real-time power allocation considering both power source degradation and system operational efficiency. The simulation results demonstrate that compared to single-layer MPC and the Equivalent Consumption Minimization Strategy (ECMS), the proposed method exhibits significant advantages in reducing single-voyage costs, minimizing differences in power source degradation rates, and alleviating power source stress. The overall performance of this strategy approaches the global optimal solution obtained through Dynamic Programming, comprehensively validating its superiority in simultaneously optimizing system economics and durability.

Impact of axial segregation characteristics on the particle collision energy in rotating drums - Qiuhua Miao; Wenchang Zhu; Yifei Ding; Peng Huang; Chaobin Hu; Yang Ge (Minerals Engineering, 2024)

A novel rejuvenation approach to improve rooting capacity and its mechanism in Cunninghamia lanceolata - Yunni Chang; Ting Xue; Josep Peñuelas; Jordi Sardans; JunXin Zhou; Yang Zhou; Chaobin Xu; XueYan Zheng; WangXun Peng; Yanbing Deng; Quanlin Zhong; Baoyin Li (Forest Ecology and Management, 2024)

Multi-omics reveal the effects and regulatory mechanism of dietary neutral detergent fiber supplementation on carcass characteristics, amino acid profiles, and meat quality of finishing pigs - Siyu Lu; Yixue Xu; Xinhui Song; Jingyi Li; Jiaqi Jiang; Chaobin Qin; Kening Wu; Kuiqing Cui; Yang Liu; Qingyou Liu; Shuibao Shen; Zhipeng Li (Food Chemistry, 2024)

(−)-Epigallocatechin-3-O-gallate or (−)-epicatechin enhances lipid catabolism and antioxidant defense in common carp (Cyprinus carpio L.) fed a high-fat diet: Mechanistic insights from the AMPK/Sirt1/PGC-1α signaling pathway - Jiali Mi; Dan Liu; Chaobin Qin; Xiao Yan; Liping Yang; Xinxin Xu; Guoxing Nie (Aquaculture, 2024)

Identification of Isthmin‐1 in common carp ( Cyprinus carpio L. ) and the effects on glucose metabolism in vivo and in vitro - Leya Qu; Liping Yang; Yiran Wang; Shaoyang Zhi; Mengjuan Zhao; Jinrui Xiong; Xiao Yan; Chaobin Qin; Guoxing Nie (Journal of Fish Biology, 2024)
Isthmin‐1 (Ism1) plays roles in glucose uptake in mammals as an adipokine. To investigate its role in the glucose metabolism of common carp ( Cyprinus carpio. L), the Ism1 sequence was cloned, and its expression and distribution in tissues were detected. In addition, we prepared and purified the recombinant Ism1 protein using the E. coli expression system and assessed changes in the expression of key genes related to glucose metabolism through both in vivo injection experiments and primary hepatocyte experiments in vitro. The results revealed that the open reading frame of Ism1 was 1377 bp long, encoding 458 amino acids. Similarity analysis indicated that Ism1 exhibited a close evolutionary relationship with goldfish ( Carassius auratus ), sharing 98.35% amino acid similarity. Ism1 was expressed in all tissues of common carp, with the highest level observed in the heart, followed by the gill, head kidney, and hepatopancreas. Distinct patterns of Ism1 expression were identified during the oral glucose tolerance test and long‐term high‐carbohydrate and high‐fat diet feeding experiments. In vivo studies demonstrated that the serum glucose concentration was reduced on treatment with Ism1, accompanied by a significant upregulation of mRNA levels for gk , hk , and pfk genes in hepatopancreas; conversely pepck and g6pase mRNA levels were significantly downregulated in the hepatopancreas under these conditions as well. Furthermore, our primary hepatocyte experiment confirmed that Ism1 could inhibit pepck and g6pase mRNA expression, while promoting gk , hk , and pfk mRNA expression levels. In conclusion, Ism1, in common carp, could participate in the glucose metabolism, which provides essential information for future studies on the function of Ism1.

Comparison of muscle nutritional composition, texture quality, carotenoid metabolites and transcriptome to underling muscle quality difference between wild-caught and pond-cultured Yellow River carp (Cyprinus carpio haematopterus) - Luming Wang; Jinrui Xiong; Chunchu Xu; Chaobin Qin; Yuru Zhang; Liping Yang; Shaoyang Zhi; Jianxin Feng; Guoxing Nie (Aquaculture, 2024)

Improvement of sea buckthorn (Hippophae rhamnoides L.) flavonoids on the antioxidant and immune performance of Yellow River carp (Cyprinus carpio L.) fed high-carbohydrate diet - Xiao Yan; Peng Pang; Chaobin Qin; Jiali Mi; Liping Yang; Bowen Yang; Guoxing Nie (Fish & Shellfish Immunology, 2024)

Establishment and characterization of Yellow River carp (Cyprinus carpio haematopterus) muscle cell line and its application to fish virology and immunology - Shaoyang Zhi; Junli Wang; Yiran Wang; Liping Yang; Chaobin Qin; Xiao Yan; Mengjuan Zhao; Mingyu Liu; Leya Qu; Guoxing Nie (Fish & Shellfish Immunology, 2023)

Impact of refined 2D/3D urban morphology on hourly air temperature across different spatial scales in a snow climate city - Chaobin Yang; Tong Kui; Weiqi Zhou; Junfu Fan; Lizhi Pan; Weiwei Wu; Min Liu (Urban Climate, 2023)

Molecular identification of glucose transporter 4: The responsiveness to starvation, glucose, insulin and glucagon on glucose transporter 4 in common carp ( Cyprinus carpio L .) - Liping Yang; Shaoyang Zhi; Guokun Yang; Chaobin Qin; Xiao Yan; Mingming Niu; Wenlei Zhang; Mingyu Liu; Mengjuan Zhao; Guoxing Nie (Journal of Fish Biology, 2021)
Glucose transporter 4 (GLUT4) is comprehensively investigated in mammals, while the comparative research of GLUT4 in common carp is deficient. To investigate the function of GLUT4, carp glut4 was first isolated. The open reading frame of carp glut4 was 1518 bp in length, encoding 505 amino acids. A high‐sequence homology was identified in carp and teleost, and the phylogenetic tree displayed that the carp GLUT4 was clustered with the teleost. A high level of glut4 mRNA was analysed in fat, red muscle and white muscle. After fasting treatment, glut4 mRNA expression was increased significantly in muscle. In the oral glucose tolerance test experiment, glut4 mRNA was also significantly elevated in muscle, gut and fat. Furthermore, intraperitoneal injection of insulin resulted in the upregulation of glut4 gene expression significantly in white muscle, gut and fat. On the contrary, the glut4 mRNA level in the white muscle, gut and fat was markedly downregulated after glucagon injection. These results suggest that GLUT4 might play important roles in food intake and could be regulated by nutrient condition, insulin and glucagon in common carp. Our study is the first to report on GLUT4 in common carp. These data provide a basis for further study on fish GLUT4.

Nitrogen, phosphorus and potassium fertilization promotes Zanthoxylum armatum ‘Hanyuan Putao Qingjiao’ flower bud differentiation in Sichuan, China - Chaobin Zhou; Yu Cai; Zhen’an Yang; Hongmin Wang; Fang Deng; Zeping Bai; Wei Gong; Jingyan Wang (Horticulture, Environment, and Biotechnology, 2020)

Molecular identification of grass carp igfbp2 and the effect of glucose, insulin, and glucagon on igfbp2 mRNA expression - Guokun Yang; Wenli Zhao; Chaobin Qin; Liping Yang; Xiaolin Meng; Ronghua Lu; Xiao Yan; Xianglin Cao; Yanmin Zhang; Guoxing Nie (Fish Physiology and Biochemistry, 2020)

Glucose transporter 2 in common carp (Cyprinus carpio L.): molecular cloning, tissue expression, and the responsiveness to glucose, insulin, and glucagon - Dapeng Deng; Xiao Yan; Wenli Zhao; Chaobin Qin; Guokun Yang; Guoxing Nie (Fish Physiology and Biochemistry, 2020)

China’s wetland databases based on remote sensing technology - Fengqin Yan; Xingtu Liu; Jing Chen; Lingxue Yu; Chaobin Yang; Liping Chang; Jiuchun Yang; Shuwen Zhang (Chinese Geographical Science, 2017)

The effect of deforestation on the regional temperature in Northeastern China - Lingxue Yu; Shuwen Zhang; Junmei Tang; Tingxiang Liu; Kun Bu; Fengqin Yan; Chaobin Yang; Jiuchun Yang (Theoretical and Applied Climatology, 2015)